A distribution method for bullwhip reduction. (19th June 2008) - Eftekhar, Mahyar; Makui, Ahmad; Lumsden, Kenth
The distortion in demand, known as the bullwhip effect, is crucial in supply chain management. On the other hand, Crossdocking is an operating strategy that moves items through flow consolidation centres (crossdocks) without putting them into storage. This logistics technique eliminates the storage and order picking functions while still allowing the system to serve its receiving and shipping functions. In this paper, the impact of crossdocking on bullwhip effect is shown. The fundamental objective in our work is to reduce the company dependency on forecasting for bullwhip reduction and introduction crossdocking as proper distribution method for bullwhip reduction.